THE EFFECT OF CLUSTERING TECHNIQUE ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS HASANAH PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Ade Yunita; Fadly Azhar; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This pre-experimental study is aims at finding out if there is a significant effect of Clustering Technique on the ability of the second year students of MTs Hasanah Pekanbaru in writing descriptive texts. The design of the study is one group pre-test post-test design. 33 students of class VIII.1 were chosen as the sample by using cluster random sampling technique. The instrument of the study was a writing test in the form of free writing. The students’ scores were analyzed by using SPSS (Statistical Package for the Social Sciences) 23.00 for windows. The result of the data analysis showed that the mean score of pre-test was 51.87 and the mean score of post-test was 73.08. In other words, the mean score of post-test was higher than the mean score of pre-test. The result showed that the value of t-test was higher than t-table (17.136>2.037) at the significant level of 5%. Therefore, alternative hypothesis is accepted and null hypothesis is rejected. It can be concluded that there is a significant effect of Clustering Technique on the ability of the second year students of MTs Hasanah Pekanbaru in writing descriptive texts.Key Words: Effect, Clustering Technique, Writing Ability, Descriptive Text